2021
DOI: 10.1149/1945-7111/ac035a
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Non-Uniform Anode Particle Morphology on Lithium-Ion Cell Performance

Abstract: The present works deals with the implications of non-uniform anode particle morphology on charging and discharging characteristics of Lithium-ion cell, especially for ultra-fast charging applications. The one-dimensional isothermal model is employed to analyze the effect of C-rate, porosity, tortuosity, and particle geometry for a range of non-uniform anode particle size distribution numerically. Our study reports that the value of capacity and specific power of the cell is found to be maximum when the particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This is attributed to the doctor blade-induced larger particle size and broader particle size distribution in the electrodes, as well as the higher density of the electrodes, which act together to decrease the active surface area, and thus the utilization of sulfur. Slurry atomization through the spray coating technique creates smaller and more uniformly sized particles, as well as a more open structure due to the multilayer arrangement of particles, which favors a faster conversion reaction, leading to better material utilization and higher capacity. …”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the doctor blade-induced larger particle size and broader particle size distribution in the electrodes, as well as the higher density of the electrodes, which act together to decrease the active surface area, and thus the utilization of sulfur. Slurry atomization through the spray coating technique creates smaller and more uniformly sized particles, as well as a more open structure due to the multilayer arrangement of particles, which favors a faster conversion reaction, leading to better material utilization and higher capacity. …”
Section: Resultsmentioning
confidence: 99%
“…This non-uniformity in particle size distribution in porous electrodes likely induces variation in transport characteristics. Note that the "Reference Case" is the one in which particle size distribution is uniform at the cathode, while the anode particle distribution is taken non-uniform and adopted from our earlier work [47]. Herein, it can be noted from Fig.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Optimizing the particle size in porous electrodes will help to maximize the energy and power density and fast charging capability. [ 127 ]…”
Section: Applications To Libsmentioning
confidence: 99%
“…Appian et al [123] simulated the electrochemical performance of Li In addition to modeling electrodes with different kinds of active materials, simulating the same active materials with different particle geometries might also be very useful to further optimize the electrode performance. [35,108,126,127] It was found that small particles are preferred for fast charging as compared to the larger particles. [35,126] This effect is related to Li diffusion inside electrodes.…”
Section: Blending Active Materialsmentioning
confidence: 99%